Taking Care of Digital Collections and Data: ‘Curation’ and Organisational Choices for Research Libraries - Angevaare, Inge (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2009)
This article explores the types of digital information research libraries typically deal with and what factors might influence libraries’ decisions to take on the work of data curation themselves, to take on the responsibility for data but market out the actual work, or to leave the responsibility to other organisations. The article introduces the issues dealt with in the LIBER Workshop ‘Curating Research’ to be held in The Hague on 17 April 2009 ( http://www.kb.nl/curatingresearch) and this corresponding issue of LIBER Quarterly.